Acute and chronic toxicity of cadmium on the copepod Pseudodiaptomus annandalei: A life history traits approach. - Kadiene, E.U., P.J. Meng, J.S. Hwang & S. Souissi (Chemosphere, 2019)
We determined the effect of acute and chronic toxicity of cadmium (Cd) on Pseudodiaptomus annandalei, according to their developmental and reproductive stages. Firstly, to estimate the 50% lethal concentration (LC50), acute exposure of nauplii and copepodids to 20, 40, 80, 150, and 300 μg/L of Cd was tested, and the effects of 5 μg/L and 40 μg/L of Cd on copepod developmental rate was done. Female lifespan and number of nauplii produced were compared. Secondly, one generation of copepod was exposed to dissolved (WCd) and dietary (DCd) Cd, and sex-specific Cd uptake and population density were estimated. 96 h LC50 was 40 μg/L Cd for nauplii and 120 μg/L Cd for copepodids. Duration of copepod development was 3.5 days and 5.5 days longer than the control when exposed to 5 μg/L and 40 μg/L of Cd, respectively. Female lifespan in both treatments were 9 and 8 days shorter than in the control, respectively. Total number of nauplii produced per female lifespan was 440 (control), 450 (5 μg/L Cd), and 365 (40 μg/L Cd). Cd uptake in copepods increased from nauplii to adults when exposed to dietary Cd and decreased when exposed to dissolved Cd. Dietary uptake of Cd was significantly higher in males than in females and Cd uptake from water was higher in males than in females, but not statistically significant. The total population of copepods were significantly affected by Cd. The toxic effects of Cd in copepods appear to depend on developmental stage, sex, duration and uptake route.